The Impact of Structured Kangaroo Care Education on Premature Infants’ Weight Gain, Breastfeeding and Length of Hospitalization in Malaysia - Sharmiza, Samsudin; Chui, Ping Lei; Azanna, Ahmad Kamar; Khatijah Lim, Abdullah *; Yu, Chye Wah; Zainah, Mohamed (Dove Press, 2023)
Purpose Kangaroo care is a complementary humanistic intervention based on a family-centered care model. This study investigated the effects of a locally contextualized, structured kangaroo care education program on weight gain, breastfeeding rate and length of hospitalization for premature infants.